Modulation of Caloric Responses by the Otolithic Organs: Implications for Vestibular Function and Fall Prevention in Bipedal Humans - Longridge, NS; Mallinson, AI; Pothier, DD; Rutka, J (Medical Science: Trends and Innovations Vol. 6, 2025)
Objective: It has been documented in the literature that caloric responses are reduced, but not absent with the lateral semicircular canal in a horizontal position. This chapter addresses what contributions to the caloric response are made by the macula of the utricle and saccule, and their contribution to how the vestibular system functions in Earth’s only bipedal mammal. This study has also discussed the complexity of balance maintenance, emphasizing the importance of the poorly understood striated organelle (STO). This structure is a contractile protein complex and is fundamental to balance function in all animals and up to now, its significance in the only mammalian biped has previously been poorly appreciated and almost disregarded. Methods: This study is a prospective case series which was arranged and conducted at a tertiary and quaternary care teaching hospital. Two normal subjects underwent “horizontal” calorics to document caloric response with the lateral semicircular canal in the horizontal position. This assessment was also carried out on eight sequential patients who were documented to have otolithic disease (as documented by abnormal VEMP assessment). Two sets of caloric tests (standard and horizontal) were carried out on our subjects. Patients underwent identical caloric assessment after CVEMP and OVEMP assessment. VEMPs were scored as either normal or abnormal for each parameter assessed. Caloric tests were scored using the standard slow-phase velocity measurements for each one. Results: Patients with otolithic abnormalities showed different caloric results in the horizontal position than is suggested in the literature and was shown by our two normal subjects. Conclusions: Caloric responses are modulated by head position and in patients with otolithic pathology, semicircular canal function is further modulated, as caloric responses are different in patients than in normals when the lateral semicircular canal orientation to gravity is changed. Our results suggest that the otoliths mediate caloric responses.